Analisis Kebijakan Desentralisasi Politik Dalam Mewujudkan Daerah Otonomi Baru di Seram Utara Kabupaten Maluku Tengah - Suatrat, Fatimah; Mahulauw, Syaifulrijal; Tehuayo, Johan (Jurnal Ilmiah Global Education, 2024)
The research entitled Analysis of Political Decentralization Abominations in Creating a New Autonomous Region in North Maluku Central Horrors, uses a qualitative descriptive method to describe how Decentralised Political Policy creates a new autonomous region in the Middle Maluku North Horror. The study uses conciliation policy theory, the theory of political decentralization, and regional autonomy as well as the theories of political authority, using indicators of the authority of local governments in making political decisions, strategic formulation of planning of regional development programmes, and budget accommodation in budgeting. Increased public service and empowerment of the community, as well as public participation, and prospects for the development of the North Horrors Region.The results of the survey showed that the various political decisions implemented by the Government of India in the framework of regional development were political decisions related to the development of indigenous villages or administrative villages, political decisions relating to the construction of new villages in order to promote regional development and political decisions involving local governments and the DPRD in the context of emergency development and rural development. Furthermore, in connection with the planning strategy of various regional construction programmes implemented by the Regional Planning Agency, the aim is to prevent inter-emergency arrangements and in order to improve the well-being of the people in the various districts of disaster that exist in the Central Maluku.